2015
DOI: 10.1007/s10237-015-0679-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the aortic valve leaflets on the fluid-dynamics in aorta in presence of a normally functioning bicuspid valve

Abstract: In this work, we consider the blood fluid-dynamics in the ascending aorta in presence of a normally functioning bicuspid aortic valve (BAV). In particular, we perform an unsteady finite element study in real geometries with physiological velocity boundary conditions at the inlet to assess the effect of the inclusion of the leaflets on the fluid-dynamic abnormalities characterizing BAV cases. To this aim, we perform a comparison in two geometries (a dilated and a non-dilated ones) among three scenarios which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 48 publications
3
17
2
Order By: Relevance
“…Previous studies showed that the open systolic configuration of the BAV leaflets is sufficient to recreate the abnormal aortic hemodynamics associated (Bonomi et al 2015). Since the goal of this work was to study BAV related ascending hemodynamics at systole, BAV leaflets were reconstructed in a fixed peak systolic configuration.…”
Section: Data Acquisition and Model Generationmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that the open systolic configuration of the BAV leaflets is sufficient to recreate the abnormal aortic hemodynamics associated (Bonomi et al 2015). Since the goal of this work was to study BAV related ascending hemodynamics at systole, BAV leaflets were reconstructed in a fixed peak systolic configuration.…”
Section: Data Acquisition and Model Generationmentioning
confidence: 99%
“…Velocity vectors and vorticity fields were captured at sections A2 and A3. Aortic flow helicity was quantified using the positive helix fraction (PHF) index (Cao et al 2017;Bonomi et al 2015),…”
Section: Hemodynamic Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these indices, it is possible to identify the type of aneurysm presented in each patient (Table 1). According to [1,[31][32][33][34][35], based on the TAA shape, different criteria for the TAA collapsibility can be applied: (i) if the TAA diameter is 45% higher than the non-deformed aorta diameter; (ii) if the asymmetry index factor is < 0.4; (iii) if the deformation diameter ratio > 3 × ; and (iv) if the saccular index < 0.6. However, the TAA dilation and potential rupture also depend on the hemodynamic loads.…”
Section: Discussionmentioning
confidence: 99%